Simmel on the Autonomy of Social Forms - Salem, A (Sociologija. Mintis ir veiksmas, 2012)
Abstract. This article argues that Simmel’s theories about modern society and culture provide important insights into the issue of the autonomy of the systems that we live under. It begins with a discussion of his ideas about a sense of unity between the self and the external world. It continues by examining the process by which such a sense alters as life fragments into the autonomous formal systems associated with modernity. This leads into an analysis of these forms and their internal functioning. The article concludes with an outline of how these considerations may be relevant to conscious efforts to bring about progressive social change. At issue is how far such critical practice can have an effect on its own terms and how far it is incorporated into a closed system incapable of affecting its environment.Keywords: action and agency, autonomous systems, personal life, social change, social critique, social forms, socio-cultural theory.